Community Empowerment To Improve Clean And Healthy Living Behavior [Chlb]: An Action Research - Hamzah Hasyim; Samsuryadi; Mulyadi Eko Purnomo; Bimo Brata Adhitya; Nur Alam Fajar; Hendro Cahyono (International Journal Of Community Service, 2021)
Efforts to change people's behaviors to support the improvement of health status are carried out through the Clean and healthy living behavior (CHLB) development program. Although this program has been implemented by the Ministry of Health in Indonesia since 1996, CHLB implementation has not run optimally. Evaluation of CHLB development's success is carried out by looking at CHLB indicators, one of which is in the school setting. CHLB at school is an activity to empower students, teachers, and the school community to adopt a healthy lifestyle to create healthy schools. This study aims to increase the students' knowledge, attitudes, and actions regarding CHLB in Madrasah Diniyyah, Al Islam Educational Institution, Talang Aur Village, Ogan Ilir Regency, South Sumatra Province.The study uses action research. This activity is carried out by providing communication, information, and education (KIE) regarding CHLB. In addition, we offer knowledge tests about CHLB and demonstrations by practicing how to wash hands correctly and adequately using clean water and soap to increase students' understanding of CHLB activities. This study emphasizes the importance of socializing clean and healthy life early through integrating learning programs in schools. The results showed an increase in the target audience's knowledge, attitudes, and actions about CHLB. The benefits of CHLB in schools include creating a clean and healthy environment, improving the teaching, and learning process, and making students, teachers, and the school environment healthy.